Interplay between Ovine Bone Marrow Stromal Cell Antigen 2/Tetherin and Endogenous Retroviruses - Arnaud, Frederick (American Society for Microbiology (ASM), 2010)
Endogenous betaretroviruses (enJSRVs) of sheep are expressed abundantly in the female reproductive tract and play a crucial role in conceptus development and placental morphogenesis. Interestingly, the colonization of the sheep genome by enJSRVs is likely still ongoing. During early pregnancy, enJSRV expression correlates with the production of tau interferon (IFNT), a type I IFN, by the developing conceptus. IFNT is the pregnancy recognition signal in ruminants and possesses potent antiviral activity. In this study, we show that IFNT induces the expression of bone marrow stromal cell antigen 2 (BST2) (also termed CD317/tetherin) both in vitro and in vivo. The BST2 gene is duplicated in ruminants. Transfection assays found that ovine BST2 proteins (oBST2A and oBST2B) block release of viral particles produced by intact enJSRV loci and of related exogenous and pathogenic jaagsiekte sheep retrovirus (JSRV). Ovine BST2A appears to restrict enJSRVs more efficiently than oBST2B. In vivo, the expression of BST2A/B and enJSRVs in the endometrium increases after day 12 and remains high between days 14 and 20 of pregnancy. In situ hybridization analyses found that oBST2A is expressed mainly in the endometrial stromal cells but not in the luminal and glandular epithelial cells, in which enJSRVs are highly expressed. In conclusion, enJSRVs may have coevolved in the presence of oBST2A/B by being expressed in different cellular compartments of the same organ. Viral expression in cells unable to express BST2 may be one of the mechanisms used by retroviruses to escape restriction.